EVALUATION OF TEACHER’S PEDAGOGICAL COMPETENCE IN IMPROVING EDUCATION QUALITY AT THE EDUCATION AND CULTURE OFFICE OF BOLAANG MONGONDOW UTARA REGENCY - Arifin Tahir; Frista Iin Wahyuni; Estefina Poluan (LP2M Universitas Bina Mandiri Gorontalo, 2022)
The purpose of this research is: 1) to find out and analyze the Evaluation of teacher’s pedagogical competence in improving education quality at the Education and Culture Office of Bolaang Mongondow Utara Regency; 2) to find out and analyze the factors that affect teacher’s pedagogical competence in improving education quality at the Education and Culture Office of Bolaang Mongondow Utara Regency. This research uses a descriptive approach through qualitative research methods. The results showed that: 1) teacher’s pedagogical competence in improving education quality at the Education and Culture Office of Bolaang Mongondow Utara Regency is good, however, several indicators need improvement; 2) the factors that influence the pedagogical competence of PAUD teachers are individual and environmental factors.